METHODS OF FORMING A READING CULTURE AMONG STUDENTS (Scientific journal of the Fergana State University, 2025)
This article focuses on improving reading skills and culture, and discusses improving reading skills and culture. The role of reading culture in the formation of reading skills, spiritual and intellectual potential, conscious thinking and worldview in younger schoolchildren is analyzed.